Kepamongprajaan Education System - Rahmawati Sururama (Publikasi Indonesia, 2023)
The civil servant education system is an educational process used to improve the quality of civil servant human resources so as to create good government. However, the civil service education system has not been studied in depth, especially at one of the civil service schools in West Java province which has been operating for quite a long time. For this reason, researchers want to study the civil service education system so that they can find out the existing civil service education system at civil service schools in the city that carry out civil service education at other civil service schools. The research method used is qualitative with data collection techniques through observation, interviews and surveys, then the data received is processed in depth to determine the research results. The results of this research show that there are 8 standards in the education system, namely content standards, process standards, graduate competency standards, teacher and education staff standards, facilities and infrastructure standards, management standards, financing standards and assessment standards. Each of these standards already has good value, but there are several things that need to be improved immediately, such as management standards and facilities and infrastructure standards so that they can support learning well and achieve educational goals effectively and efficiently because each of these standards has different values. Good. an interrelated relationship. with other people.